2014
DOI: 10.1097/cad.0000000000000082
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3G exerts tumor suppressive effects in human hepatocellular carcinoma

Abstract: In this study, we collected 44 hepatitis B virus surface antigen positivity HBsAg (+) tumor and nontumor hepatocellular tissues from hepatocellular carcinoma (HCC) patients during hepatectomy, and quantified the APOBEC3G (A3G) mRNA by using a real-time PCR. Our results showed higher expression of A3G mRNA in the nontumor tissues than in the tumor tissues of the HBsAg (+) HCC patients. To further investigate this phenomenon, we constructed a pLV-A3G vector and transfected it into the human HCC cell line, Hep 3B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Due to the gene redundancy across immune gene sets, we identified “core genes” (genes associated with the enrichment signal) over-represented in different subsets for immune biological processes. The top-ten rank core genes included APOBEC3G (Apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like 3G) that exerts innate immune activity against retroviruses and has shown tumor suppressive effects in human hepatocellular carcinoma and enhance cell radio resistance in lymphomas; [ 8 , 9 ] APOBEC3F (Apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like 3F) that showed to inhibit HIV-1 DNA Integration; [ 10 ] CCL5 (Chemokine (C-C motif) ligand 5, a well characterized chemotactic chemokine; CD1D (CD1d molecule) mediate the presentation of self or microbial antigens to T cells; LAT (Linker for activation of T cells), a major transporter for essential amino acids into activated human T cells; [ 11 ] TRAT1 (T cell receptor associated transmembrane adaptor 1), important to transport od CTLA-4 to the cell surface; [ 12 ] IL32 (Interleukin 32), whose expression is increased after the activation of T-cells by mitogens or the activation of NK cells by IL-2; CRTAM (cytotoxic and regulatory T cell molecule), upregulated in CD4 and CD8 T cells; CFHR1 (complement factor H-related 1), whose protein product binds to Pseudomonas aeruginosa elongation factor Tuf together with plasminogen and CCR2 (chemokine [C-C motif] receptor 2) that mediates monocyte infiltration. The complete list of core genes involved in immune gene sets is shown in Table S3 .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the gene redundancy across immune gene sets, we identified “core genes” (genes associated with the enrichment signal) over-represented in different subsets for immune biological processes. The top-ten rank core genes included APOBEC3G (Apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like 3G) that exerts innate immune activity against retroviruses and has shown tumor suppressive effects in human hepatocellular carcinoma and enhance cell radio resistance in lymphomas; [ 8 , 9 ] APOBEC3F (Apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like 3F) that showed to inhibit HIV-1 DNA Integration; [ 10 ] CCL5 (Chemokine (C-C motif) ligand 5, a well characterized chemotactic chemokine; CD1D (CD1d molecule) mediate the presentation of self or microbial antigens to T cells; LAT (Linker for activation of T cells), a major transporter for essential amino acids into activated human T cells; [ 11 ] TRAT1 (T cell receptor associated transmembrane adaptor 1), important to transport od CTLA-4 to the cell surface; [ 12 ] IL32 (Interleukin 32), whose expression is increased after the activation of T-cells by mitogens or the activation of NK cells by IL-2; CRTAM (cytotoxic and regulatory T cell molecule), upregulated in CD4 and CD8 T cells; CFHR1 (complement factor H-related 1), whose protein product binds to Pseudomonas aeruginosa elongation factor Tuf together with plasminogen and CCR2 (chemokine [C-C motif] receptor 2) that mediates monocyte infiltration. The complete list of core genes involved in immune gene sets is shown in Table S3 .…”
Section: Resultsmentioning
confidence: 99%
“…While similar suppressive effects on tumor cell growth have been reported for APOBEC3G [27], the widely accepted main oncogenic function of APOBEC3s is an induction of genome hypermutation [2]. There are therefore 2 scenarios to explain our findings.…”
Section: Discussionmentioning
confidence: 51%
“…29 , 30 However, another in vitro study found that high APOBEC3G expression reduced the migration ability of human hepatocellular carcinoma cells. 31 APOBEC3G gene and protein expression was significantly more abundant in melanoma compared to adjacent normal tissues, and its higher expression was associated with longer overall and recurrence‐free survival. Moreover, APOBEC3G expression is positively correlated with the infiltration of B cells, CD8+ T cells, macrophages, neutrophils, and dendritic cells.…”
Section: Discussionmentioning
confidence: 97%
“…In colorectal cancer, APOBEC3G tissue protein expression was associated with poor prognosis and suggested to be mechanistically involved in the formation of liver metastasis 29,30 . However, another in vitro study found that high APOBEC3G expression reduced the migration ability of human hepatocellular carcinoma cells 31 . APOBEC3G gene and protein expression was significantly more abundant in melanoma compared to adjacent normal tissues, and its higher expression was associated with longer overall and recurrence‐free survival.…”
Section: Discussionmentioning
confidence: 99%